Analisis aktivitas antelmintik ekstrak etanol daun Mimosa pudica L. terhadap Ascaridia galli - Tresnani, Galuh; Martini, Rima; Pratama, Iman Surya (University of Mataram, 2022)
Mimosa pudica leaves contain of metabolites such as tannin, flavonoid and alkaloid which have the anthelmintic effects. This effect would be expected to minimalize the infection of parasitic worm Ascaridia galli in chicken. The research aim was to determine the effectivity of ethanol extract from mimosa leaves to A. galli worm in vitro. Mimosa leaves were extracted using maceration process. Worm samples were grouped randomly, consist of the positive control (Piperazine 1%), negative control (CMC Na 0.5%) and the treatment groups (10%, 20% and 50% of extract concentration). Mortality and paralysis data from the worm samples were collected and analyzed using Kruskal Wallis and Mann Whitney Test. The phytochemical analysis showed that mimosa leaves extract contains all the secondary metabolite which can cause paralysis and mortality of A. galli. The 50% concentration of mimosa leaves extract can cause paralysis in 90 minutes equal with the positive control. The mortality time achieved by positive control, 50%, 20% and 10% of ethanol extract of mimosa leaves sequentially as follows 120, 270, 645 and 780 minutes. In conclusion, 50% mimosa leaves extract concentration have the best effect of anthelmintic, the paralysis effect equal with Piperazine but the mortality time is still slower than Piperazine.